Reading Arab Women’s Autobiographies: Shahrazad Tells Her Story by Nawar Al-Hassan Golley (Austin: University of Texas Press, 2003. 236 pages.) (American Journal of Islam and Society, 2006)
In writing Reading Arab Women’s Autobiographies: Shahrazad Tells HerStory, Nawar Al-Hassan Golley’s goal is to fill a critical gap. Recent bookslike Marilyn Booth’s May Her Likes Be Multiplied: Biography and GenderPolitics in Egypt (Berkeley: University of California Press, 2001) analyzewomen’s relation to biography from Zainab Fawwaz’s Scattered Pearls (1894) onward. However, any critical analysis of Arab women’s autobiographyis scarce, if not non-existent. In its efforts to fill this critical gap, ReadingArab Women’s Autobiographies carves out a dual readership. Delineatingpast and present meanings both within and without Islam of “Arab,” “Arabworld,” “hijab,” and “harem” with an eye to the non-Arab reader, Golley’sanalysis of five autobiographical texts and three anthologies of women’s collectedstories simultaneously participates in a conversation with other Arabwomen scholars about modes of text production, distribution, and the overallplace of women’s autobiography within Arab feminism.Part 1, “Political Theory: Colonial Discourse, Feminist Theory, andArab Feminism,” contains three chapters: “Why Colonial Discourse?”;“Feminism, Nationalism, and Colonialism in the Arab World”; and “HudaShaarawi’s Harem Years: The Memoirs of an Egyptian Feminist.” In the firsttwo, the author argues for the inclusion of gender-related issues within colonialdiscourse analysis and for the necessity of adopting Spivak’s “strategicessentialism” when speaking of “Arab women.” In outlining a brief historyof Arab feminism, Golley strives to both demystify the “aura of exoticism”that has surrounded Arab women and to demonstrate that Arab feminism “isnot alien to Arab culture.” ...